Penggunaan Strategi Number Head Together dengan Media Kartu Bergambar Untuk Meningkatkan Hasil Belajar Materi Ekosistem pada Siswa Kelas V MIS Riyadhul Ulum Sui Bakau Besar Mempawah - Saumi Setyaningrum; Umar Hasib (Didaktika: Jurnal Kependidikan, 2022)
The purpose of this study is to find out how to describe: 1) how to use the number head together strategy with picture card media. 2) how are the results of learning ecosystem materials before using the number head together strategy with picture card media. 3) what are the thematic learning outcomes after using the number head together strategy with picture card media. 4) whether there is an increase in thematic learning outcomes after using the number head together strategy with picture card media for the ecosystem material for class V MIS Riyadhul Ulum students for the 2020/2021 school year. This research was designed using Class Room Action Research (CAR) with three cycles, quantitative data analysis and quantitative analysis. Based on the analysis carried out, the researchers found that: 1) The implementation of the number head together strategy with picture card media for class V students of MIS Riyadhul Ulum Sui Bakau Darat in the 2020/2021 academic year in cycle I could be carried out 71.43%, cycle II was carried out 85 ,71% and cycle III carried out 90.48% of the learning steps carried out. 2) The results of thematic learning before using the number head together strategy with picture card media for ecosystem component materials in cycles I and II were 0% of students who completed while in cycle II there were 4% of students who achieved complete scores. 3) Thematic learning outcomes after using the number head together strategy with picture card media on ecosystem materials in the first cycle was 48%, the second cycle was 72% and the third cycle was 84% ​​of students achieving a complete score. 4) The increase in learning outcomes for ecosystem materials after using the number head together strategy with picture cards media for ecosystem materials from cycle I to cycle II increased by 24%, from cycle II to cycle III it increased 12% while from cycle I to cycle III it increased 36% activities.